CONCEPTUALIZING L2 VOCABULARY KNOWLEDGE: AN EMPIRICAL EXAMINATION OF THE DIMENSIONALITY OF WORD KNOWLEDGE - González-Fernández, Beatriz (Studies in second language acquisition, 2022)
The multidimensional conceptualization of vocabulary knowledge has been extraordinarily influential in lexical research. Yet, the few studies that have empirically explored the structure of word knowledge conflict regarding its multidimensionality. The present study examines the nature of L2 vocabulary knowledge by exploring how the hypothesized word-knowledge dimensions fit together across different L2 learner groups. A total of 314 EFL learners from two dissimilar L1 backgrounds (Chinese n = 170; Spanish n = 144) were assessed using eight vocabulary measures testing recognition and recall knowledge of form-meaning, collocations, multiple meanings, and derivatives. Confirmatory factor analysis (CFA) revealed that vocabulary knowledge behaves as a unidimensional construct for each learner group individually. Simultaneous multigroup CFA confirmed that this unidimensional model holds invariant across the two groups regardless of their distinct L1s. These findings provide empirical evidence for the unidimensionality of vocabulary knowledge in a second language, indicating the need to refine the conceptualization of the construct.